(untitled) (International Journal of Engineering and Computer Science, 2014)
In this paper, the structure of video capture system based on S3C2440 processor is presented. And the embedded system, video capture, short message service (SMS) alarm, and client video monitor are introduced. Video 4 Linux is used to get the camera video data, which is transferred to the Web Server, and the data is displayed on the client browser. The system can also be connected with mobile phones, using SMS to control alarm equipment. The system can be applied in intelligent anti-theft, intelligent transportation, intelligent home, medical treatment, as well as all kinds of video surveillance systems. Compared with video capture system based on digital signal processor (DSP), this system has the advantages of fewer modules, lower cost, higher intelligence, higher system stability, and higher security. With the development of Broad Band, computer networks, and image processing technology, video capture has been widely used in image acquisition, security, health care, intelligent community, alarm, transportation and so on. But it also has many problems, such as high cost, low intelligence, poor stability, weak security. In order to solve these problems, S3C2440 microprocessor is adopted in this embedded video Acquisition system which is combined with the Linux operating system. Video capture is realized by the Video 4 Linux.